Retrieval of Bard Simon Nitinol inferior vena cava filters: Approaches, technical successes, complications, and clinical outcomes. (August 2021) - Bundy, Jacob J; Chick, Jeffrey Forris Beecham; Srinivasa, Ravi N; Cooper, Kyle J; Gemmete, Joseph J; Wadhwa, Vibhor; Moriarty, John M
Objective: The Simon Nitinol filter is a bi-level filtration device designed for permanent implantation that is no longer commercially available, but may result in similar complications to current commercially available long term indwelling temporary or permanent filters. Complications related to indwelling inferior vena cava filters include inferior vena cava thrombosis, inferior vena cava penetration, filter migration, and filter fracture. There is a paucity of reports describing the technical aspects related to retrieval of Simon Nitinol filters. Materials and methods: This study consisted of five patients with Simon Nitinol filters and describes the indication for retrieval, the retrieval techniques used to remove the filters, technical success, complications, and clinical course. Results: The indications for retrieval included: abdominal pain ( n = 2; 40%), iliocaval thrombosis ( n = 1; 20%), identification of an intracardiac filter fragment ( n = 1; 20%), and recurrent venous thromboembolic events ( n = 1; 20%). Retrieval techniques included: biopsy forceps ( n = 3; 60%), excimer laser extraction sheaths ( n = 3; 60%), hangman modified loop snares ( n = 3; 60%), rigid endobronchial forceps ( n = 2; 40%), and balloon deflection ( n = 2; 40%). All filters were successfully retrieved. One patient developed a post-procedural intramuscular hematoma near the site of right internal jugular sheath placement. Conclusions: Simon Nitinol filters may be retrieved safely and effectively using advanced inferior vena cava filter retrieval techniques.